Expresionismo Alemán. - Bartsch, Ingo; Herzog, Hans-Michael; Hülsewig-Johnen, Jutta; Centro Atlántico de Arte Moderno, Las Palmas de Gran Canaria (Las Palmas : Centro Atlantico de Arte Moderno Las Palmas de Gran Canaria, 1995)
Barlach, Ernst ; Beckmann, Max ; Campendonk, Heinrich ; Corinth, Lovis ; Dix, Otto ; Erbslöh, Adolf ; Feininger, Lyonel ; Felixmüller, Conrad ; Gramatté, Walter ; Heckel, Erich ; Jawlensky, Alexej von ; Kirchner, Ernst Ludwig ; Kollwitz, Kathe ; Kottenkamp, Paul ; Macke, August ; Meidner, Ludwig ; Morgner, Wilhelm ; Mueller, Otto ; Münter, Gabriele ; Nolde, Emil ; Ophey, Walter ; Pechstein, Max ; Rohlfs, Christian ; Schmidt-Rottluff, Karl ; Stenner, Hermann
bibliografie
biografie
Engels & Duits
Spaans
Expresionismo Alemán, Centro Atlantico de Arte Moderno Las Palmas de Gran Canaria, 14 de noviembre de 1995 - 7 de enero de 1996
boek
Keywords: Duitsland